2015
DOI: 10.1371/journal.pone.0124522
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Fluctuation Score for Parkinson's Disease

Abstract: IntroductionEstablishing the presence and severity of fluctuations is important in managing Parkinson’s Disease yet there is no reliable, objective means of doing this. In this study we have evaluated a Fluctuation Score derived from variations in dyskinesia and bradykinesia scores produced by an accelerometry based system.MethodsThe Fluctuation Score was produced by summing the interquartile range of bradykinesia scores and dyskinesia scores produced every 2 minutes between 0900-1800 for at least 6 days by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 10 publications
(8 reference statements)
1
70
0
2
Order By: Relevance
“…The finding that the median BKS and median DKS closely correlate with the UPDRS III and mAIMS support the contention that the original algorithms can classify motor symptoms as rated by an objective observer [7] and can distinguish between fluctuating and non-fluctuating patients [19]. Thus the mismatch seems more likely to be between the objective and subjective observer.…”
Section: Discussionmentioning
confidence: 57%
“…The finding that the median BKS and median DKS closely correlate with the UPDRS III and mAIMS support the contention that the original algorithms can classify motor symptoms as rated by an objective observer [7] and can distinguish between fluctuating and non-fluctuating patients [19]. Thus the mismatch seems more likely to be between the objective and subjective observer.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, we collected data in defined medication states: after 12 hour withdrawal of antiparkinsonian medications ("off"), and after a suprathreshold dose of levodopa/carbidopa ("on"). The on-medication state was associated with the expected reduction in subthalamic beta band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz) activity in each individual case (Figure 3c) and across all 16 subthalamic recordings (p < 0.001, Generalized Estimating Equations (GEE)) (Fig 3d). Thus, acute effects of levodopa observed previously with externalized leads were validated here by wireless data transmission from an implanted device, recorded 2-4 weeks after surgery.…”
Section: Data Characteristics Movement Related Activity and Effect mentioning
confidence: 95%
“…Short term testing using externalized leads has suggested that adaptive DBS could offer improved efficacy 10 and reduced adverse effects 11 compared with standard, continuous DBS. There is a candidate biomarker for bradykinesia identified from acute, peri-operative recordings from externalized leads: the amplitude of beta band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz) oscillatory activity in basal ganglia field potential recordings 2 . However, cortical biomarkers of parkinsonian motor signs have also been proposed [12][13][14] and it is not known which site (cortical or basal ganglia) is most effective for motor state decoding.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, none of the available detection systems fulfill all of the criteria defined herein . However, the most advanced systems have begun to generate target parameters that are easy to understand (individual scores) and that have a great potential to complement the information needed to improve therapeutic decisions . Because this review cannot be comprehensive, we include illustrative examples of useful technology‐based systems that assess PD features.…”
Section: Which Pd Features Should Be Prioritized In the Development Omentioning
confidence: 99%
“…Moreover, PD patients with suboptimal (oral) medication compliance are at higher risk of developing exacerbated PD symptoms than are patients who comply, and poor medication compliance is relatively common in PD, especially among young patients with many doses/day and depressed patients . Technology‐based assessment of motor fluctuations has been demonstrated with a simple and easy‐to‐use system, including a proposal for a target range to differentiate between motor and nonmotor fluctuations and a retrospective analysis of the clinical effects of the system …”
Section: Which Pd Features Should Be Prioritized In the Development Omentioning
confidence: 99%